The complete mitochondrial genome of the red flour beetle, Tribolium castaneum (Coleoptera: Tenebrionidae). (3rd March 2016) - Liu, Qiu-Ning; Bian, Dan-Dan; Jiang, Sen-Hao; Li, Zhen-Xing; Ge, Bao-Ming; Xuan, Fu-Jun; Yang, Li; Li, Chao-Feng; Zhang, Dai-Zhen; Zhou, Chun-Lin; Tang, Bo-Ping
Abstract: The complete mitochondrial genome (mitogenome) of Tribolium castaneum (Coleoptera: Tenebrionidae) was determined to be 15, 883 bp (GenBank accession No. KM009121), which contains 22 tRNA genes, 13 protein-coding genes (PCGs), 2 rRNA genes and a major non-coding A + T-rich region. It has the typical gene organization and order of mitogenomes from ancestral insects. The nucleotide composition was also biased toward A + T nucleotides (71.72%) and the AT skew of this mitogenome was slightly positive. All of the 22 tRNA genes displayed a typical clover-leaf structure, with the exception of trnS1 (AGN). Thirteen PCGs were initiated by ATN codons, except for cytochrome c oxidase subunit 1 ( cox1 ) gene which was initiated by AAT. Eight of the 13 PCGs harbor the incomplete termination codon by T or TA. The A + T-rich region of the mitogenome was 1237 bp in length and the A + T content was 82.30%.